Stock price reaction to dividend announcement: An empirical study on Dhaka Stock Exchange (DSE) - Zahan, Arafat; Rana, Md. Shohel (Journal of Management, Economics, and Industrial Organization, 2020)
The major objective of this study is to identify whether dividend announcement convey any information to the market that results a price reaction. With the objectives in mind, this paper used only secondary data from DSE. The study comprised a total of 21 companies these are listed by DSE. The research is only quantitative in nature. The empirical part of this study employs a standard ‘event study methodology’ to analyze the stock price reaction to dividend announcement. With the help of ‘event study methodology’ MAAR and CAAR to analyze the effect of dividend announcement on stock prices taking 21 listed companies of Dhaka Stock Exchange (DSE) in Bangladesh. The results were showed by using chart, table, descriptive statistics and t-statistics. The finding indicates that some companies are efficient, and some are inefficient. The results are statistically significant both before declaration date and after declaration date. In this paper, before declaration date of third and eight are efficient and after declaration date of five and eight are inefficient.